“I Stay Because of My Students“: Urban Lower Secondary School Teachers' Experiences of Belonging at Work - Martin Skogheim (Nordic Journal of Comparative and International Education, 2023)
This study explores urban lower secondary school teachers’ sense of belonging, focusing on their relationships with students and their work experiences. Despite heightened interest in students’ sense of belonging in educational settings, empirical research on teacher belonging – especially in the context of urban lower secondary education – remains sparse. The limited focus on teachers’ experiences of belonging at work is paradoxical, given their crucial role in fostering student belonging and the global challenges regarding the recruitment and retention of teachers. While previous research on belonging has underscored its importance for job satisfaction, professional identity development, and motivation at work, there has been a lack of focus on understanding how student-teacher relationships specifically influence teachers’ experiences of belonging to their school. This study draws from interviews and observational data to gain a deeper understanding of teachers’ day-to-day practice. It gives voice to the reflections and experiences of teachers and leaders. The findings emphasize the critical role of reciprocal student–teacher relationships through three interrelated themes. Relationships of this nature not only foster student development but also enhance teachers’ sense of belonging. The study also highlights the importance of supportive collegial relationships. In particular, teachers report strong experiences of belonging when their identity as teachers and individual contributions resonate with their school’s values and educational goals.